1975
DOI: 10.1007/bf01634148
|View full text |Cite
|
Sign up to set email alerts
|

An other look at iron: Role in host pathogen interaction

Abstract: Iron, as participant of many biological processes is a prerequisite for life. Uptake, internal transport and storage by organisms is handled by highly specialized chemical systems endowed with strong metal binding affinities. Apart from the homeostatic function of iron-binding compounds they appear of significance for inter-species interactions. Thus, by tight binding transferrin withholds the iron from invading microorganisms required for their optimal growth. This bacteriostatic property of the iron transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…A low Fe status has marked effects on immune reactions and infection rates in calves (Gygax et al., 1993) and may mediate its effects through modification of NO formation. Conversely, a high Fe intake can have detrimental effects because the proliferation of pathogenic bacteria can be enhanced (Ganzoni and Puschmann, 1970). Furthermore, there may be detrimental effects by a high Fe status if the production of molecular oxygen or of NO is enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low Fe status has marked effects on immune reactions and infection rates in calves (Gygax et al., 1993) and may mediate its effects through modification of NO formation. Conversely, a high Fe intake can have detrimental effects because the proliferation of pathogenic bacteria can be enhanced (Ganzoni and Puschmann, 1970). Furthermore, there may be detrimental effects by a high Fe status if the production of molecular oxygen or of NO is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…(1993) demonstrated that the administration of Fe‐citrate increased endotoxin‐induced NO formation and effects in diverse organs of mice. A low Fe status, which is frequent in veal calves due to low Fe intake by milk and milk replacers (Lindt and Blum, 1993, 1994), can both markedly influence immune reactions and infection loads (Ganzoni and Puschmann, 1970; Sherman, 1984; Heresi, 1985; Bhaskaram, 1988), as has been shown in calves (Gygax et al., 1993). Thus, in Fe‐deficient calves the activity of the Fe‐containg enzyme of neutrophils was reduced and infection rates were enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the latter studies (183), good correlation of extent of depression with Hb value was observed; for example, mean percentages of formation of rosettes in T cells of children with Hb levels of >12, 10 to 12, 8 to 10, and <8 g/dl, respectively, were 58.7, 54.3, 47.3, and 37.9. Thus, a few patterns are beginning to emerge concerning the status of nonspecific and immune defenses in the iron-poor host. However, at this stage of our developing knowledge, caution is advised in extrapolation of in vitro laboratory tests to the in vivo situation (50,73). Recent WHO Technical Reports on nutritional anemias (4, 4a) described the etiological role of hemorrhagic nematodal and trematodal infestation in iron deficiency, but contained only fragmentary information on interactions of iron nutrition with either bacterial, fungal, or protozoan infections.…”
Section: Effiect Of Iron On Phagocytosis and Immune Responses Iron Exmentioning
confidence: 99%
“…The infection-enhancing effect of hemoglobin was found to be due to ferric ions and could be duplicated with ferric ammonium citrate (2,5,33). The importance of iron to host defense mechanisms and to invading bacteria has been described for experimental infections with a variety of organisms, primarily facultative gramnegative rods (4,6,14,15,24,29,30,32,33,37). Although most authors feel that the enhancing effect of hemoglobin depends on the iron and its activity as a microbial nutrilite, others believe that hemoglobin acts by interfering with the clearance of viable bacteria from the peritoneal cavity (10, 34), for example, by inhibition of chemotaxis of phagocytes (20 VOI,.…”
Section: Discussionmentioning
confidence: 99%